2013
DOI: 10.3324/haematol.2013.084350
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and prognostic impact of oligoclonal humoral response in patients with multiple myeloma after autologous stem cell transplantation: long-term results from a single institution

Abstract: The emergence of an oligoclonal humoral response, resulting in the appearance of a different serum M-protein to that observed at diagnosis is a well-recognized event after autologous stem cell transplantation in multiple myeloma in complete response, and it has been considered to be a benign phenomenon. The aim of the present study was to investigate the incidence, biological characteristics and prognostic value of the oligoclonal bands in patients with myeloma who underwent autologous transplantation at our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 25 publications
7
64
2
1
Order By: Relevance
“…Further, information about isotype and electrophoretic migration position is needed when following response to therapy so that one may distinguish relapse of the original clone from the development of oligoclonal bands and/or a second (usually reactive) M-protein. Such additional M-proteins commonly occur after autologous stem cell transplants with rates as high as 73% being reported [7][8][9][10]. The development of oligoclonal bands and/or a second M-protein following autologous stem cell transplantation in MM has been reported to be a favorable prognostic sign for most patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Further, information about isotype and electrophoretic migration position is needed when following response to therapy so that one may distinguish relapse of the original clone from the development of oligoclonal bands and/or a second (usually reactive) M-protein. Such additional M-proteins commonly occur after autologous stem cell transplants with rates as high as 73% being reported [7][8][9][10]. The development of oligoclonal bands and/or a second M-protein following autologous stem cell transplantation in MM has been reported to be a favorable prognostic sign for most patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…4,9 Several studies also showed a higher frequency of sMGUS in patients treated with novel agents when compared to conventional chemotherapy. 7,16,17 Importantly, sMGUS is not a sign of relapse or progression of MM. 3,17,19,20 In fact, some studies found that patients who develop sMGUS have a superior prognosis in terms of progression-free survival (PFS) and overall survival (OS) than those without sMGUS.…”
Section: Introductionmentioning
confidence: 99%
“…7,16,17 Importantly, sMGUS is not a sign of relapse or progression of MM. 3,17,19,20 In fact, some studies found that patients who develop sMGUS have a superior prognosis in terms of progression-free survival (PFS) and overall survival (OS) than those without sMGUS. 1,2,4,6,9,10,[12][13][14]17 However, other studies, often with a small sample size, concluded that the presence of sMGUS does not relate to the prognosis of MM, or that it is only associated with a better response and not with a benefit in terms of PFS or OS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations